Comorbidities, treatment, and pathophysiology in restless legs syndrome. Issue 11 (November 2018) - Trenkwalder, Claudia; Allen, Richard; Högl, Birgit; Clemens, Stefan; Patton, Stephanie; Schormair, Barbara; Winkelmann, Juliane
Summary: Restless legs syndrome, also known as Willis-Ekbom disease, is a common neurological condition whose manifestation is affected by complex environmental and genetic interactions. Restless legs syndrome can occur on its own, mostly at a young age, or with comorbidities such as cardiovascular disease, diabetes, and arterial hypertension, making it a difficult condition to properly diagnose. However, the concept of restless legs syndrome as being two entities, primary or secondary to another condition, has been challenged with genetic data providing further insight into the pathophysiology of the condition. Although dopaminergic treatment was formerly the first-line therapy, prolonged use can result in a serious worsening of symptoms known as augmentation. Clinical studies on pregabalin, gabapentin enacarbil, oxycodone–naloxone, and iron preparations have provided new treatment options, but most patients still report inadequate long-term management of symptoms. Studies of the hypoxic pathway activation and iron deficiency have provided valuable information about the pathophysiology of restless legs syndrome that should now be translated into new, more effective treatments for restless legs syndrome.